Специфіка порівняльних підходів уметодології досліджень сучасних міграційних процесів в Європі - Блажевська, Є.В.; Блажевская, Е. В.; Blazhevska, Ye.V. (Одеса : Фенікс, 2017)
На початку XXI століття міграційні процеси у зв’язку з активною глобалізацією набули надзвичайно широких масштабів; складність такого явища часто призводить до протиріч між інтересами держави і/або світової спільноти і правами окремої людини, етнічної групи, нації. З огляду на серйозну значущість проблеми є досить актуальним проведення різними інститутами крос-національних порівняльних досліджень в цій галузі, для чого необхідно в тому числі дослідити понятійно-категоріальний апарат цієї сфери, відмінний в різних країнах і регіонах світу, і, можливо, створити на міжнародному рівні новий загальноприйнятий апарат для більшої ефективності дослідницької діяльності.

Вначале XXI века миграционные процессы в связи с активной глобализацией приобрели чрезвычайно широкие масштабы; сложность данного явления часто приводит к противоречиям между интересами государства и/или мирового сообщества и правами отдельного человека, этнической группы, нации. Учитывая серьезную значимость проблемы представляется весьма актуальным проведение различными институтами кросс-национальных сравнительных исследований в этой области, для чего необходимо в том числе исследовать понятийно-категориальный аппарат этой сферы, отличный в разных странах и регионах мира, и, возможно, создать на международном уровне новый общепринятый аппарат для большей эффективности исследовательской деятельности.

At the beginning of the XXI century a noticeable transformation of migra-tion processes is observed under the influence of globalization, which effect the change of social, cultural, spiritual and economic models of different countries and world regions more and more actively. This stipulates the necessity for host countries to improve migration policies for more effective control over economic, social and cultural advantages or, vice versa, disadvantages, which international migration brings with it. Consequently, the necessity of constant examination of this problem seems logical, including the level of cross-national comparative researches, during which the study of the same phenomenon in two or more countries in various socio-cultural conditions with the us-age of the same tools takes place. Taking into consideration the variable and unpredictable nature of the problem, the necessity of the stable basis for such researches is transparent, first of all, the need of permanent generally accepted and used conceptual and categorical apparatus, which predetermines primary importance of the research of this apparatus in the field of migration; in this context, the analysis of using of the terms “migrant” and “ethnic minority” in the scientific political and social discourses of such countries, as Canada, Great Britain and Germany is given in the case of this article.
Блажевська Є. В. Специфіка порівняльних підходів уметодології досліджень сучасних міграційних процесів в Європі / Є. В. Блажевська // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. редкол.), Л. І. Кормич (голов. ред.), А. В. Полухіна (відп. ред.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2017. – Вип. 59. – С. 53-60.
Keywords: міграційні процеси; термін «мігрант»; термін «іммігрант»; миграционные процессы; термин «мигрант»; термин «иммигрант»; term "immigrant"; migration processes; the term "immigrant"; Research Subject Categories::LAW/JURISPRUDENCE